Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1158/1535-7163.mct-20-0087
|View full text |Cite
|
Sign up to set email alerts
|

Combined Targeting of the BRD4–NUT–p300 Axis in NUT Midline Carcinoma by Dual Selective Bromodomain Inhibitor, NEO2734

Abstract: NUT midline carcinoma (NMC) is a rare, aggressive subtype of squamous carcinoma that is driven by the BRD4-NUT fusion oncoprotein. BRD4, a BET protein, binds to chromatin through its two bromodomains, and NUT recruits the p300 histone acetyltransferse (HAT) to activate transcription of oncogenic target genes. BET-selective bromodomain inhibitors have demonstrated on-target activity in patients with NMC, but with limited efficacy. P300, like BRD4, contains a bromodomain. We show that combining selective p300/CB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 36 publications
1
57
0
Order By: Relevance
“…These data indicate that NEO2734 and NEO1132 would be good candidates for combinational drug studies in MM and maybe potentially beneficial in reducing resistance in MM and restoring sensitivity to immunomodulatory drugs in relapse/refractory MM patients. NEO2734, unlike JQ1, has been shown to be tolerated well in preclinical animal models 37‐41 . Taken together, these data indicate the potential value of the novel dual inhibitors, NEO2734 and NEO1132, as a single‐drug double‐hit approach for treating a broad range of MM and warrant further clinical investigation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These data indicate that NEO2734 and NEO1132 would be good candidates for combinational drug studies in MM and maybe potentially beneficial in reducing resistance in MM and restoring sensitivity to immunomodulatory drugs in relapse/refractory MM patients. NEO2734, unlike JQ1, has been shown to be tolerated well in preclinical animal models 37‐41 . Taken together, these data indicate the potential value of the novel dual inhibitors, NEO2734 and NEO1132, as a single‐drug double‐hit approach for treating a broad range of MM and warrant further clinical investigation.…”
Section: Discussionmentioning
confidence: 82%
“…Due to these issues several JQ1 derivatives have been developed for clinical applications, among them are OTX015 and I‐BET762, which we also included in our study, these have been shown to be tolerated well in early phase clinical trials as therapies for hematologic malignancies including MM (see ClinicalTrials.gov). Unlike JQ1, NEO2734 is tolerated well in mice indicating, although highly potent, NEO2734 has the potential to be taken forward into clinical trials 37,40,41 …”
Section: Discussionmentioning
confidence: 99%
“…Through unbiased signaling pathway inhibitor survey, we demonstrate that ENZ-R cells are hyper-sensitive to the dual inhibitors of BET and CBP/p300 proteins such as NEO2734 [50][51][52] . In agreement with these results, we show that chromatin occupancy of CXXC5 and H3K27ac levels are positively correlated at noncanonical AR target loci and that the BET-CBP/p300 dual inhibitor treatment inhibits CXXC5 protein expression and decreases BRD4 and p300 binding and H3K27ac levels at these loci.…”
Section: Discussionmentioning
confidence: 98%
“…We found that the combination of the BET inhibitor and WEE1 inhibitor had additive effects on NMC. Moreover, a recent report showed that the combination therapy targeting BET and p300, which belongs to writers and acetylates histone lysine residues, was more effective than BET inhibitor alone [42]. Given the epigenetic categories in histone modi cation, the combination of BET inhibitors and target inhibitors in another epigenetic category might be useful for the treatment of NMC.…”
Section: Discussionmentioning
confidence: 99%